Principles of Risk Management and Insurance - Rejda G. E. George (Global Edition)
The Global Edition of Principles of Risk Management and Insurance, 12e, is the market-leading text for this course. With a focus on the consumers of insurance, this text blends basic risk management and insurance principles with consumer considerations. This Global Edition has been edited to include enhancements making it more relevant to students outside the United States. The editorial team at Pearson has worked closely with educators around the globe to include: Updated! Discussion of life insurance marketing: The section on life insurance marketing and distribution systems has been completely updated and substantially rewritten. New! Insight boxes: The twelfth edition contains a number of new and timely Insight boxes. New! Health-Care Reform: Coverage of the broken healthcare delivery system in the U.S.